Distribution of blaOXA Genes in Acinetobacter baumannii Strains: A Multicenter Study - Ciftci, Ihsan Hakki; Asik, Gulsah; Karakece, Engin; Oksuz, Lutfiye; Yagci, Server; Cetin, Emel Sesli; Ayyildiz, Ahmet (Ankara Microbiology Soc, 2013)
Acinetobacter baumannii is the most important agent of nosocomial infections within the Acinetobacter genus. This gram-negative coccobacillus is intrinsically resistant to many antibiotics used in antimicrobial therapy, and capable of developing resistance including carbapenems. The objective of this study was to develop a multiplex real time polymerase chain reaction (qPCR) kit for OXA subgroups in A.baumannii, and to investigate the distribution of OXA subgroups in A.baumannii strains isolated from geographically different regions of Turkey. A total of 834 A.baumannii clinical isolates collected from different state and university medical centers in 13 provinces (Afyonkarahisar, Ankara, Bolu, Elazig, Erzurum, Isparta, Istanbul, Kahramanmaras, Konya, Sakarya, Van) between 2008-2011, were included in the study. The isolates were identified by conventional methods and automated systems [Vitek2 (bioMerieux, ABD) and Phoenix (BD Diagnostic, MD)]. The susceptibility profiles of the isolates were studied with automated systems and standard disc diffusion method. All samples were subjected to qPCR to detect bla(OXA-51-like), bla(OXA-23-like) and bla(OXA-58-like) genes. A conventional PCR method was also used to detect bla(OXA-24-like) gene. The resistance rates observed during the study period were as follows: 96.8% for amoxicillin-clavulanate, 86.8% for ciprofloxacin, 74.7% for gentamicin, 71.7% for amikacin, 73.5% for cefaperozone-sulbactam, 72.1% for imipenem and 73% for meropenem. Six hundred and two (72.2 %) isolates were resistant to both imipenem and meropenem. Colistin was found to be the most effective antibiotic against A.baumannii isolates with 100% susceptibility rate. All isolates were positive for bla(OXA-51-like) gene, however bla(OXA-24-like) gene could not be demonstrated in any isolate. Total positivity rates of bla(OXA-23-like) and bla(OXA-58-like) genes were found as 53.7% and 12.5%, respectively, while these rates were 74.4% and 17.3% in carbapenem-resistant isolates, respectively. Twenty-five isolates were positive-for both bla(OXA-23-like) and bla(OXA-58-like) genes. All of the carbapenem-resistant isolates have OXA type genes like with the exception of bla(OXA-24-like) gene. The positivity rates for bla(OXA-23-like) and bla(OXA-58-like) genes varied for each center. In addition, there was a decrease in the frequency of bla(OXA-58-like) gene, however both bla(OXA-23-like) gene and carbapenem resistance rates increased during the study period. In conclusion, high rates of resistance to carbapenems were also remarkable but A.baumannii strains keep on sensitivity to colistin. Both bla(OXA-23-like) and bla(OXA-58-like) genes were shown to be widespread in carbapenem-resistant A.baumannii clinical isolates. However, bla(OXA-23-like) gene positive strains were increased throughout the study. Currently, multiplex qPCR is the best way for rapid diagnosis of resistant bacteria for prevention of hospital-acquired infections. The multiplex qPCR kit developed in this study could be useful for rapid diagnosis and identify the frequencies of bla(OXA-23-like), bla(OXA-51-like) and bla(OXA-58-like) genes in carbapenem-resistant A.baumannii clinical isolates.
Acinetobacter baumonnii izolatlannda blaOXA genlerinin da?ilimi: Çok merkezli bir çalişma
Keywords: Acinetobacter baumannii; carbapenem resistance; OXA; multiplex real-time PCR